2016
DOI: 10.1093/mnrasl/slw148
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in globular cluster streams: giant molecular clouds can cause them too

Abstract: As a result of their internal dynamical coherence, thin stellar streams formed by disrupting globular clusters (GCs) can act as detectors of dark matter (DM) substructure in the Galactic halo. Perturbations induced by close flybys amplify into detectable density gaps, providing a probe both of the abundance and of the masses of DM subhaloes. Here, we use N-body simulations to show that the Galactic population of giant molecular clouds (GMCs) can also produce gaps (and clumps) in GC streams, and so may confuse … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 51 publications
5
98
0
Order By: Relevance
“…In the Newtonian framework, such a large leading -trailing arm asymmetry, which is observed for the Palomar 5 stream in the Pan-STARRS data (provided it is not due to extinction), can only be the consequence of interactions with dark matter subhalos (Erkal et al 2016), giant molecular clouds (Amorisco et al 2016), or interaction with a prograde Galactic bar. In all these Newtonian cases, the asymmetry is the consequence of a very large gap, due to the disruption of the pre-existing stream.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In the Newtonian framework, such a large leading -trailing arm asymmetry, which is observed for the Palomar 5 stream in the Pan-STARRS data (provided it is not due to extinction), can only be the consequence of interactions with dark matter subhalos (Erkal et al 2016), giant molecular clouds (Amorisco et al 2016), or interaction with a prograde Galactic bar. In all these Newtonian cases, the asymmetry is the consequence of a very large gap, due to the disruption of the pre-existing stream.…”
Section: Resultsmentioning
confidence: 98%
“…However, the Newtonian orbits necessary to reproduce the Pal 5 stream never produce large asymmetries. External perturbations which could cause such asymmetries in Newtonian dynamics include fly-by of compact objects, such as DM subhaloes or giant molecular clouds (Erkal et al 2016;Amorisco et al 2016) that removed the stars initially present in the leading arm, or a prograde rotating bar in the frame of the stream (Pearson et al 2017). Of course such effects (apart from those of DM subhaloes) could also exist in MOND, but the key point is that they all create a very large gap in the stream, whilst we would like hereafter to check if the EFE of MOND can on the other hand lead to a true asymmetry.…”
Section: Simulating the Palomar 5 Stream In Mondmentioning
confidence: 99%
“…An additional effect, particularly relevant for Pal-5, is the potential confusion of perturbations by substructures with those induced by giant molecular clouds. These are, of course, relatively slow moving, and Amorisco et al (2016) point out that they induce perturbations similar to those caused by dark matter subhaloes.…”
Section: Substructure Detection Via Stream Gapsmentioning
confidence: 96%
“…Follow-up medium-resolution spectroscopy obtained by Koposov et al (2010) showed that GD-1 has a relatively circular but retrograde orbit, with a pericenter at 14 kpc and an apocenter at 26 kpc. This orbit keeps the system well away from the inner regions of the Galactic disk, where interactions with giant molecular clouds could cause additional heating (Amorisco et al 2016), that could contaminate the sought-for signal from ΛCDM substructure.…”
Section: The Gd-1 Streammentioning
confidence: 99%